Mad men & bad men what happened when British politics met advertising - Sam Delaney (London Faber & Faber, 2015)
From the moment Margaret Thatcher met the Saatchi brothers, elections campaigns would never be the same again. Suddenly, every aspiring PM wanted a fast-talking, sharp-thinking ad man on their team to help dazzle voters. But what were the consequences of their fixation with the snappy and simplistic?
Includes bibliographical references (pages 269-274) and index.
Keywords: Great Britain. Parliament -- Elections -- History -- 20th century; Great Britain. Parliament -- Elections -- History -- 21st century; Political campaigns -- Great Britain -- History -- 20th century; Political campaigns -- Great Britain -- History --21st century; Advertising, Political -- Great Britain -- History -- 20th century; Advertising, Political -- Great Britain -- History -- 21st century; Elections -- Great Britain -- History -- 20th century; Elections -- Great Britain -- History -- 21st century